Mesenchymal stem cell therapy improves spatial memory and hippocampal structure in aging rats - Zappa Villar, María Florencia (2019)
There is a growing interest in the potential of mesenchymal stem cells (MSCs) for implementing regenerative medicine in the brain as they have shown neurogenic and immunomodulatory activities. We assessed the effect of intracerebroventricular (icv) administration of human bone marrow-derived MSCs (hBM-MSCs) on spatial memory and hippocampal morphology of senile (27 months) female rats, using 3-months-old counterparts as young controls. Half of the animals were injected in the lateral ventricles (LV) with a suspension containing 5 × 105hBM-MSCs in 8 μl per side. The other half received no treatment (senile controls). Spatial memory performance was assessed with a modified version of the Barnes maze test. We employed one probe trial, one day after training in order to evaluate learning ability as well as spatial memory retention. Neuroblast (DCX) and microglial (Iba-1 immunoreactive) markers were also immunohistochemically quantitated in the animals by means of an unbiased stereological approach. In addition, hippocampal presynaptic protein expression was assessed by immunoblotting analysis. After treatment, the senile MSC-treated group showed a significant improvement in spatial memory accuracy and extended permanence in a one- and 3-hole goal sectors as compared with senile controls. The MSC treatment increased the number of neuroblasts in the hippocampal dentate gyrus, reduced the number of reactive microglial cells, and restored presynaptic protein levels as compared to senile controls. We conclude that icv injected hBM-MSCs are effective in improving spatial memory in senile rats and that the strategy improves some functional and morphologic brain features typically altered in aging rats.